Particle swarm optimization aplicada ao planejamento da expansão de sistemas de transmissão - Resende, Adriana Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work, two methodologies to solve the transmission network expansion planning (TNEP) problem have been proposed. The first one is a presentation of a meta-heuristic based algorithm, Particle Swarm Optimization (PSO), as a tool to solve static TNEP problems. In this proposition, the mathematical models of transportation model and the DC model have been used. Both the models have been implemented via the programming language of FORTRAN and the commercial solver of MINOS has been used to solve the related LP problems. The second proposal, presents the TNEP problem considering multiple generation scenarios using the disjunctive linear model. This model has been implemented via AMPL and solved by the commercial solver of CPLEX. In order to validate and qualify the first proposed methodology, five case studies have been carried out, these cases are: Garver, IEEE 24-bus, Southern Brazil, Colombian, and Brazilian North-Northeast systems. And for the second proposed methodology, 3 case studies have been used such as: Garver, IEEE 24-bus and Southern Brazil test systems. The results show the effectiveness and the usefulness of the proposed methodologies

Neste trabalho, são propostas duas metodologias para resolver o problema de planejamento da expansão de sistemas de transmissão (PPEST). A primeira delas é uma apresentação de um algoritmo baseado em meta-heurística, Particle Swarm optimization (PSO), como ferramenta para resolver o PPEST estático. Nesta proposta são usados os modelos matemáticos de transporte e CC. Ambos os modelos foram implementados na linguagem de programação FORTRAN e o solver comercial MINOS foi usado para resolver os problemas de programação linear relacionados. A segunda proposta apresenta o PPEST considerando múltiplos cenários de geração usando o modelo linear disjuntivo. Este modelo foi implementado via AMPL e resolvido usando o solver comercial CPLEX. A fim de validar e qualificar a primeira metodologia proposta, cinco sistemas foram estudados, são eles: Garver, IEEE 24-barras, Sul Brasileiro, Colombiano e Norte-Nordeste Brasileiro. E para a segunda metodologia proposta, três sistemas foram estudados, são eles: Garver, IEEE 24-barras, Sul Brasileiro. Os resultados mostraram a eficiência e utilidade das duas metodologias propostas
Keywords: Energia eletrica - Transmissão; Sistemas de energia eletrica; Planejamento; Electric power systems